O léxico nos domínios da Zagaia: um estudo linguistico na Serra da Canastra - Minas Gerais - Gisele Aparecida Ribeiro (2016)
This research has as an objective analyzing the rural vocabulary of some communities embraced by the Canastra National Park, which is placed in the Southwest region in Minas Gerais state, covering the following towns: São Roque de Minas, Delfinópolis, São João Batista do Glória, Vargem Bonita and Passos. Our purpose is to show that lexicological studies point to close relation among men, culture and the environment where they are inserted. By researching the referred lexicon when speaking about this region, it is intended to get in the cultural, social, economical, religious and political universe of the inhabitants of this region and to notice in it the way of interaction among men, world and their similars through the language. As the theoretical and methodological reference it was used the Sociolinguistics (Labov and Milroy), the Lexicology and Lexicography (Matoré and Biderman), the Linguistic Anthropology (Duranti and Hymes), the Dialectology (Isquerdo e Cardoso), the concept of cultural region (Diégues Jr). Guided by the labovian model, we started from the present, by collecting our data resulted from the 32 oral interviews made in the Canastra National Park, we went back to the past, by consulting dictionaries from the XVIII (Bluteau) and XIX (Morais) centuries, and we returned to the present as to establish comparisons among these periods. After the partial linguistics analysis of the data, it was detected retention, variation and linguistics changes examples through the time, the existence of a regional vocabulary and influence examples coming from the vocabulary of the countryside of São Paulo. It was also observed common lexias in the South and in the North of Minas Gerais and also in other regions of Minas Gerais by comparing some vocabulary coming from the Projeto Léxico Regionais Mineiros (Mineiro Regional Lexicon Project). The results which were gotten till the moment, through our study, show historical, social and cultural aspects of the region, highlighting the importance of the nature and the topography of the region treated here.